The differentiation of single and dual career athletes falls short: A person-oriented approach to characterize typical objective life situations of elite athletes. Issue 3 (June 2023) - Örencik, Merlin; Schmid, Michael J.; Schmid, Jürg; Conzelmann, Achim
Research concerning athletic career development in high-performance sport typically uses demographic data, sport characteristics or pursuing a dual career (i.e. having an educational or vocational career simultaneous to the athletic career) to identify developmental processes. In defiance of these attempts, considerable heterogeneity remains within these subgroups of the elite athlete population. In line with the person-oriented approach, the objective of this study was to develop a comprehensive typology of athletes with similar objective life situations by considering both sport-related as well as non-sport related aspects. To this end, data were collected about athletic performance level, weekly amount of working time (i.e. sport-related activities, education, and vocation), and financial information (i.e. gross annual income and income generated from sport). Based on a sample of 733 elite athletes, a cluster analysis was performed to divide the sample into groups of similar patterns on the aforementioned factors. Five different athlete patterns were found: (1) working dual career athletes, (2) high-income professional athletes, (3) medium-income professional athletes, (4) family-supported athletes, and (5) student dual career athletes . These findings support the dual career literature of separating dual career ( Cluster 1 and Cluster 5 ) from single career athletes, which, in turn, should also not be regarded as a single population, but further divided ( Cluster 2, Cluster 3, and Cluster 4 ). This typology may aid federations and practitioners within athletic career development in providing individual assistance for elite athletes.